Transient Cnp expression by early progenitors causes Cre‐Lox‐based reporter lines to map profoundly different fates. Issue 2 (3rd November 2016) - Tognatta, Reshmi; Sun, Wenjing; Goebbels, Sandra; Nave, Klaus‐Armin; Nishiyama, Akiko; Schoch, Susanne; Dimou, Leda; Dietrich, Dirk
Abstract : NG2 expressing oligodendroglial precursor cells are ubiquitous in the central nervous system and the only cell type cycling throughout life. Previous fate mapping studies have remained inconsistent regarding the question whether NG2 cells are capable of generating certain types of neurons. Here, we use CNP‐Cre mice to map the fate of a sub‐population of NG2 cells assumed to be close to differentiation. When crossing these mice with the ROSA26/YFP Cre‐reporter line we discovered large numbers of reporter‐expressing pyramidal neurons in the piriform and dorsal cortex. In contrast, when using Z/EG reporter mice to track the fate of Cnp‐ expressing NG2 cells only oligodendroglial cells were found reporter positive. Using BrdU‐based birth dating protocols and inducible NG2CreER:ROSA26/YFP mice we show that YFP positive neurons are generated from radial glial cells and that these radial glial cells display temporary and low level activity of certain oligodendroglial genes sufficient to recombine the Cre‐inducible reporter gene in ROSA26/YFP but not in Z/EG mice. Taken together, we did not obtain evidence for generation of neurons from NG2 cells. Our results suggest that with an appropriate reporter system Cnp activity can be used to define a proliferative subpopulation of NG2 cells committed to generate oligodendrocytes. However, the strikingly different results obtained from ROSA26/YFP versus Z/EG mice demonstrate that the choice of Cre‐reporter line can be of crucial importance for fate mapping studies and other applications of the Cre‐lox technology. GLIA 2017;65:342–359 Main Points: Cnp activity can identify self‐renewing stage of NG2 cells committed to oligodendroglial lineage. Transient oligodendroglial gene expression by radial glial cells recombines highly sensitive Cre‐reporter genes and leads to reporter+ postnatal neurons.